Сучасні тенденції Retention-маркетингу: адаптація глобальних практик до українського контексту - Кукіна, Наталя Володимирівна; Малтиз, Вікторія Віталіївна; Kukina, Natalia; Maltyz, Viktoriia (Запоріжжя : ТДАТУ, 2024)
UA: Стаття присвячена дослідженню стратегії retention-маркетингу як ефективного інструменту утримання клієнтів в умовах українського ринку. Аналізуються ключові аспекти адаптації міжнародних практик до локальних реалій, що дозволяє підвищити конкурентоспроможність підприємств. Окрему увагу приділено структурним елементам комунікаційної політики, таким як сегментація клієнтів, персоналізація, програми лояльності та омнікальність. Висвітлюються виклики та перспективи впровадження retention-маркетингу для українських компаній у сучасному бізнес-середовищі. EN: The article is devoted to studying modern retention-marketing trends and analyzing the adaptation of global practices to the Ukrainian market. The main task of the work is to evaluate the effectiveness of retention marketing as a strategy to retain customers and increase the competitiveness of enterprises in the conditions of a changing market environment. The authors consider the key elements of a successful communication policy, which are the foundation for long-term customer interaction: customer segmentation, personalization of communications, loyalty programs, omni strategies, analytics and automation. The study highlights that today's consumers are increasingly demanding and informed. They make purchasing decisions more quickly, making predicting their long-term behaviour difficult. Technological changes and new communication platforms require companies to adapt their marketing strategies flexibly. Implementation of retention marketing allows businesses not only to retain existing customers but also to maximize their long-term value. Strategies such as loyalty programs, personalized offers, and omnichannel engagement help increase customer loyalty and drive repeat purchases. The study also provides examples of successful implementation of global practices on the Ukrainian market. In particular, companies such as Rozetka, Monobank, and EVA implement loyalty programs, but they are often limited to essential incentives such as introductory bonuses. The study revealed that Ukrainian companies do not yet fully use the possibilities of personalization based on big data, characteristic of world leaders such as Amazon Prime or Starbucks Rewards. The study's primary results are identifying essential challenges faced by Ukrainian companies. One of these challenges is the limited ability to collect and analyze large amounts of data, which prevents the creation of deeply personalized offers for each customer. In addition, the authors note that the automation of communication processes in Ukraine is just beginning to develop, and most companies still need to implement complex solutions for building trigger campaigns and personalized offers. The conclusions indicate that the adaptation of international retention-marketing practices in Ukraine is at an initial stage. However, to successfully implement such strategies, it is necessary to increase customer orientation, actively implement innovative technologies, automate processes, and use analytical tools to gain a deeper understanding of customer behaviour. The integration of these elements will allow Ukrainian companies to retain existing customers and increase their loyalty and economic efficiency thanks to repeat purchases and long-term relationships. The authors emphasize that implementing retention marketing is essential for ensuring sustainable growth and development of enterprises in the conditions of growing competition and changes in consumer behaviour.
Modern retention-marketing trends: adaptation of global practices to Ukrainian context
Keywords: retention-маркетинг; утримання клієнтів; конкурентоспроможність; маркетингова комунікаційна політика; лояльність споживачів; retention-marketing; customer retention; competitiveness; marketing communication policy; consumer loyalty